SOCIAL IDENTITY IN SECOND LANGUAGE ACQUISITION - Mahmud Layan Hutasuhut (BAHAS, 2015)
Second Language Acquisition (SLA) is the interdisciplinary field of inquirey which investigates people’s capacity to learn a second language (L2) or subsequent languages (L3, L4, etc.) once the first language (L1) has been acquired. Thus, the onset of acquisition occurs at some time during the L2 learner’s late childhood, adolescent, or adulthood years in either naturalistic (informal) or instructed (formal) settings. When the inquiry into SLA began in the late 1960s it drew equally from what was known or theorised in the fields of linguistics, psychology, language teaching and child language acquisition. In the years that ensued, SLA developed ties with the fields of anthropology, education, bilingualism, psycholinguistics and sociology, and since the mid 1990s there has been a significant theoretical shift from what was once a near exclusive concern for psycholinguistics aspects of L2 learning, or ‘language in the mind’,  to a focus on the socio-pragmatic aspects of L2 acquisition, or ‘language as situated in social contexts’ (Ellis, 2012).     Kata Kunci :      Second Language Acquisition, linguistics, psychology, language teaching